2012
DOI: 10.1371/journal.pone.0034965
|View full text |Cite
|
Sign up to set email alerts
|

Pentraxin 3 (PTX3) Expression in Allergic Asthmatic Airways: Role in Airway Smooth Muscle Migration and Chemokine Production

Abstract: BackgroundPentraxin 3 (PTX3) is a soluble pattern recognition receptor with non-redundant functions in inflammation and innate immunity. PTX3 is produced by immune and structural cells. However, very little is known about the expression of PTX3 and its role in allergic asthma.Objectives and MethodsWe sought to determine the PTX3 expression in asthmatic airways and its function in human airway smooth muscle cells (HASMC). In vivo PTX3 expression in bronchial biopsies of mild, moderate and severe asthmatics was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 66 publications
5
50
0
Order By: Relevance
“…Predominance of expression of a certain cytokine by the bronchial epithelium does not preclude a pathogenic role for the corresponding factor in other cell types and processes. In fact, several mediators involved in asthma pathophysiology, such as TGF-β [49,50], osteopontin [38,51], pentraxin-3 [52] and resistin-like molecule-β [53] are prominently expressed in the bronchial epithelium and exert effects on subepithelial cells. Interestingly, and in agreement with other studies, our findings demonstrated that activin-A is also localised in the nucleus of subepithelial cells in the bronchial mucosa, possibly reflecting other, unidentified roles for this cytokine in gene regulation [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Predominance of expression of a certain cytokine by the bronchial epithelium does not preclude a pathogenic role for the corresponding factor in other cell types and processes. In fact, several mediators involved in asthma pathophysiology, such as TGF-β [49,50], osteopontin [38,51], pentraxin-3 [52] and resistin-like molecule-β [53] are prominently expressed in the bronchial epithelium and exert effects on subepithelial cells. Interestingly, and in agreement with other studies, our findings demonstrated that activin-A is also localised in the nucleus of subepithelial cells in the bronchial mucosa, possibly reflecting other, unidentified roles for this cytokine in gene regulation [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…[12] Furthermore, increased PTX3 protein production in bronchial tissue, mainly in airway smooth muscle cells (AMSCs), was initially reported in adult asthma patients. [14] An in vitro study reported that the release of PTX3 from human AMSCs was stimulated by proinflammatory cytokines [interleukin (IL)-1β, tumor necrosis factor (TNF)], and PTX3 enhanced the release of C-C motif chemokine ligand 11 (CCL11)/eotaxin-1, which is an important chemokine in eosinophilic airway inflammation and remodeling. It is inferred that PTX3 may be involved in the pathogenesis of asthma, with the induction of CCL11/eotaxin-1 expression in inflammatory conditions affecting structural alterations in asthmatic airways.…”
Section: Discussionmentioning
confidence: 99%
“…[9] An association between PTX3 and chronic airway inflammatory diseases has been also discovered. [1014] However, the precise role of PTX3 in chronic lung inflammation has not been established, particularly in children.…”
Section: Introductionmentioning
confidence: 99%
“…A second notable gene is PTX, which encodes innate immunity protein pentraxin 3. Elevated levels of pentraxin 3 protein have been measured in the bronchial tissues of allergic asthmatic subjects and are primarily detected in ASM cells (75). Pentraxin 3 levels also become elevated in subjects with ARDS within 24 h of diagnosis, presumably as an activator of the local innate immune system in the lung (3).…”
Section: Discussionmentioning
confidence: 99%